Dissemination of Nutrition Knowledge among the Rural Women and Children for the Nutritional Security and Assessing the Perceived Socio-economic Impact - A. Janaki Rani, (Indian Journal of Extension Education, 2023)
The study was conducted in Madurai district of Tamil Nadu, India to assess the existing dietary pattern and nutritional status and nutritional requirements of women through Anthropometry, bio-chemical, clinical assessment and dietary survey methods. The results indicated that nearly 15.00 per cent of the respondents were suffering with chronic energy deficiency having less than 18.5 values of BMI. 31.67 per cent of respondents had mild anemia and 11.67 per cent were suffered with severe anemia with hemoglobin level of less than 7. About 28.00 per cent of the boys and 21.66 per cent of the girls seen to be underweight. Hence the major nutritional requirements needed for the respondents are related to iron rich foods, calcium and protein rich foods and millet based food products. To overcome the above deficiencies various extension approaches were conducted to create awareness among the rural women and children. Overall 53.37 per cent of improvement was seen in the knowledge level of the women respondents. Skill on doing value addition in major food groups has increased to 56.67 per cent. The overall perceived socio economic impact is approximately 40.00 per cent. Frequency of consumption of major foods groups and iron rich foods should be increased. Mothers of the children should be educated about the importance of balanced diet and nutritional programmes.